Facile fabrication of MoO3/g-C3N4 p-n junction for boosted photocatalytic elimination of 2, 4-D under natural sunlight exposure. Issue 5 (October 2021) - Alenazi, Duna Abdul Kaream; Aslam, M.; Chandrasekaran, S.; Soomro, M. Tahir; Ali, Shahid; Danish, Ekram Y.; Ismail, I.M.I.; Hameed, A.
Abstract: The Mo 6+ ions were primarily attached to the surface of g-C3 N4 by solution impregnation and finally transformed to oxides by calcination. The enhanced absorption in the visible region, without the appearance of multiple absorption maxima, indicated the interactive homogeneity of the material instead of the construction of distinct particles. A mild lowering in the conduction band edge elucidated the role of Mo 6+ d -orbitals in the restructuring of the conduction band. The trapping of the excitons by the coated layer was reflected in emission measurements whereas the Raman and the XRD analysis confirmed the growth of the coated layer with increasing Mo 6+ loading. The SEM and HRTEM analysis ruled out the formation of individual particles whereas the probable variations in the oxidation state of impregnated Mo 6+ were estimated by XPS analysis. Prior to the actual photocatalytic testing, the electrochemical characterization, both in the dark and under illumination, predicted the optimum performance of g-C3 N4 loaded with a 3% Mo 6+ coating layer. The Mott-Schottky analysis exposed the p-n junction nature of the material with the conduction band edges of n-type g-C3 N4 at − 1.19 V and that of p-type MoO3 at + 0.4 V in the 3% coated layer material. For the degradation of 2, 4-dichlorophenoxyacetic acid, enhanced activity of as-synthesized coated photocatalysts was observed both in the complete spectrum and visible region of natural sunlight exposure as compared to pure g-C3 N4 . An unfavorable upshot on the photocatalytic activity was perceived beyond the 3% Mo 6+ coating level that further authenticated the findings of the electrochemical analysis. The identification of 2, 4-dichlorophenol and other HO radicals substituted intermediates, both by HPLC and GC-MS analysis, exposed the major execution of HO radicals in the course whereas the open-chain intermediates verified the subsidiary role of O2 - radicals in the removal exercise. The findings extracted from various analytic tools were correlated to anticipate the conceivable mechanism of the 2, 4-D removal process. Graphical Abstract: ga1 Highlights: The surface Mo 6+ layers converted to p-type MoO3 on calcination. The p-n junction formation between the photocatalysts was confirmed by Mott-Schottky analysis. The performance of the catalysts towards the elimination of 2, 4-D increased with the coating level. The bands edge potentials of the catalysts allow the generation of HO radicals in the system. The mineralization of the substrate is verified by TOC analyses.